Polymer Advancements in Renewable Energy Technologies: Bridging Sustainability and Practicality - Wang, Chencan; Ye, Mao; Tu, Ruiting; Li, Lanjingting; Pei, Kean; Hou, Yilin (International Journal of Materials Science and Technology Studies, 2024)
Renewable energy technologies have seen substantial progress in recent years, with solar, wind, and water becoming key sustainable energy sources. Solar photovoltaic technology, in particular, has advanced significantly, driving down costs and making renewable energy more economically viable across many regions. Despite these advancements, challenges such as technological maturity, high costs, and inefficiencies in energy storage and transmission continue to hinder widespread adoption. Conductive polymers have emerged as promising materials to address these challenges, particularly in enhancing organic solar cell efficiency. Their lightweight and flexible properties make them ideal for portable and adaptable energy applications. Structural modifications, including adjustments to conjugation lengths, side chains, and the incorporation of nanomaterials, have improved light absorption, charge transport, and overall energy conversion efficiency. This review explores the critical role of polymers in renewable energy technologies, focusing on their application in solar cells, energy storage, and sustainable material design. It highlights innovative approaches to polymer development, such as nanocomposite integration and chemical modifications, which have enabled significant advancements in energy efficiency and sustainability. By addressing current challenges and uncovering future potential, this study emphasizes the importance of polymers in driving the transition to renewable energy systems.